THE DUMAI CITY GOVERNMENT POLICIES IN ENSURING THE SUSTAINABILITY OF THE LIVELIHOOD SYSTEM OF FISHING COMMUNITIES - Muhammad Isnainy Ramadhan; Zulkarnaini Zulkarnaini; Darwis Darwis (Fakultas Perikanan dan Kelautan, Universitas Riau, 2021)
There has been a decrease and increase in the number of fishermen in the last 5 yearswhich is thought to be caused by the development of an industrial area on the coast ofDumai City. This paper aims to determine the socio-economic conditions of the fishingcommunities adjacent to the Dumai City industrial area, analyze the impact of industrialdevelopment on the livelihoods of fishing communities, and analyze the Dumai CityGovernment policies in ensuring the sustainability of the livelihoods of fishingcommunities. This research was conducted using a survey method with a quantitativeapproach located in Dumai City on March - April 2021. This study reveals that thepositive impact of industrial development in the coastal area of Dumai City is theincreased consumption of capture fishery products in Dumai City and the availability ofwide employment opportunities according to the level of education required, while thenegative impact of industrial development in the coastal area of Dumai City is theincreasingly narrow fishermen's catching areas that are in accordance with the type ofboat and the type of fishing gear currently used and the occurrence of livelihood shifts.This negative impact can threaten the sustainability of the fishermen's livelihood systemin Dumai City because based on the identification of socio-economic conditions,fishermen in Dumai City have lower middle income. Based on the SWOT analysis, thealternative policy that can be carried out by the Dumai City government in ensuring thesustainability of the livelihood system of the fishing community is to carry out a capturefisheries area development program as well as fostering Joint Business Groups withfishermen and the formation of fishermen's cooperatives.